Reduced KCNQ4-encoded voltage-dependent potassium channel activity underlies impaired β-adrenoceptor-mediated relaxation of renal arteries in hypertension - Chadha, Preet S.; Zunke, Friederike; Zhu, Hai-Lei; Davis, Alison J.; Jepps, Thomas A.; Olesen, Soren P.; Cole, William C.; Moffatt, James D.; Greenwood, Iain A. (Hypertension, 2012)
KCNQ4-encoded voltage-dependent potassium (Kv7.4) channels are important regulators of vascular tone that are severely compromised in models of hypertension. However, there is no information as to the role of these channels in responses to endogenous vasodilators. We used a molecular knockdown strategy, as well as pharmacological tools, to examine the hypothesis that Kv7.4 channels contribute to β-adrenoceptor-mediated vasodilation in the renal vasculature and underlie the vascular deficit in spontaneously hypertensive rats. Quantitative PCR and immunohistochemistry confirmed gene and protein expression of KCNQ1, KCNQ3, KCNQ4, KCNQ5, and Kv7.1, Kv7.4, and Kv7.5 in rat renal artery. Isoproterenol produced concentration-dependent relaxation of precontracted renal arteries and increased Kv7 channel currents in isolated smooth muscle cells. Application of the Kv7 blocker linopirdine attenuated isoproterenol-induced relaxation and current. Isoproterenol-induced relaxations were also reduced in arteries incubated with small interference RNAs targeted to KCNQ4 that produced a ≈60% decrease in Kv7.4 protein level. Relaxation to isoproterenol and the Kv7 activator S-1 were abolished in arteries from spontaneously hypertensive rats, which was associated with ≈60% decrease in Kv7.4 abundance. This study provides the first evidence that Kv7 channels contribute to β-adrenoceptor-mediated vasodilation in the renal vasculature and that abrogation of Kv7.4 channels is strongly implicated in the impaired β-adrenoceptor pathway in spontaneously hypertensive rats. These findings may provide a novel pathogenic link between arterial dysfunction and hypertension. © 2012 American Heart Association, Inc.
CRIS-Team Scopus Importer:2020-10-21
Keywords: β-adrenoceptor; KCNQ; Kv7 channels; renal artery; spontaneously hypertensive rat; vascular smooth muscle; vasodilation